The Effect of Meteoric Phreatic Diagenesis and Spring Sapping on the Formation of Submarine Collapse Structures in the Biak Basin, Eastern Indonesia - David P. Gold (Ikatan Ahli Geologi Indonesia, 2018)
The islands of Biak and Supiori, situated in the Bird’s Head region of New Guinea, comprise predominantly Neogene age carbonate units that extend offshore into the adjacent Biak Basin. Unusual geomorphologic features including pockmarks, headless canyons and semi-circular collapse structures identified in multibeam bathymetric imagery occur on the southern margin of the Biak Basin. These features have a bathymetric expression distinct from strike-slip faults of the Biak Fault Zone which bound the eastern margin of the basin. The Biak Fault Zone comprises several seismically active, segmented and parallel fault strands. Seismicity along the Biak Fault Zone is responsible for the shedding of mass transport deposits into the basin, however these are absent from the geomorphologic features along the southern margin of the basin. Instead, these features appear isolated and unrelated to activity of the Biak Fault Zone and are interpreted to have formed as a result of ‘spring sapping’ by submarine aquifers. Rapid uplift during the Pliocene caused exposure and karstification of carbonates from onshore Biak which extend into the offshore Biak Basin, providing conduits for a freshwater lens to develop within older Miocene strata. Diagenetic cement textures and fabrics indicate that many Miocene carbonates were subjected to meteoric diagenesis within freshwater aquifers that overprinted burial cements. This is supported by stable isotope analyses of diagenetic cements which record negative δ18O values.